Treating substance abuse and mental health issues as 'mutually‐exclusive' entities: Best practice or an outmoded approach to intervention?. (17th January 2016) - Webber, Adrian; Clark, Jane; Kelly, David
Abstract: Addressing the psychological distress of individuals experiencing substance use disorders has too often been relegated to the 'too hard basket', leaving those affected with little choice but to receive treatments aimed solely at addressing their drug and alcohol issues. Conversely, individuals receiving support for psychological issues are often underdiagnosed with regards to any comorbid substance misuse problems. In fact, to date, no definitive treatment model exists that gives equal focus to the treatment of both psychological well‐being and substance‐related addictions. This is not to suggest, however, that existing treatment programmes for substance misuse are not impacting positively on clients' mental health, rather that further research is needed in order to determine what it is that is supporting such improvements. The aim of this study, therefore, was to address this imbalance by examining the correlation between substance dependence and psychological well‐being. Using a descriptive correlation design, the Severity of Dependence and Kessler 10 scales were administered to 37 inpatient and outpatient clients at a rural drug and alcohol rehabilitation service, at intake and 2 months into treatment. Data were analysed using descriptive statistics and paired‐samples t ‐tests. Positive correlative factors of improvement between substance dependence and psychological well‐being were found for both groups. In light of these findings, the authors recommend that future research be undertaken to investigate the causal factors for this correlation .